(untitled) (Universal International Scientific Journal, 2026)
In the context of rapid digitalization, television remains one of the most influential sources of information and entertainment for preschool children. This study is devoted to examining the pedagogical significance of television programs in the development of speech among preschool aged children. The main objective of the research is to analyze the impact of age-appropriate and educational television content on children’s vocabulary development, pronunciation, coherent speech, and communicative competence. The research employed pedagogical observation, comparative analysis, and interviews with preschool teachers and parents. The findings show that educational television programs rich in meaningful content, clear pronunciation, and interactive elements have a positive influence on children’s speech development. Such programs support the acquisition of new vocabulary, contribute to correct pronunciation, and encourage children to express their thoughts more freely and confidently. In addition, narrative-based programs with engaging characters expand children’s imagination and increase their communicative activity. At the same time, uncontrolled viewing and exposure to content that is not appropriate for children’s age may lead to a decrease in speech activity and limit social interaction. Passive screen time without adult guidance reduces opportunities for active communication, which is especially important during the preschool period. In conclusion, television programs can become an effective pedagogical tool in preschool education only when they are carefully selected and used in moderation.